Diversidade genética entre e dentro de populações F4 de pimenteiras ornamentais (Capsicum annuum L.) - Costa, Maria do Perpetuo Socorro Damasceno (2018)
Among the plants with potential ornamental, are the pepper plants belonging to the genus Capsicum and the family Solanaceae. Pepper ornamental potted have stood out in the ornamental market due to their characteristics aesthetic that include, among other attributes, the coloring of the fruits and leaves and harmony with the pot. The great diversity in this genus has allowed its use in breeding programs. The improvement of ornamental peppers is based mainly on the hybridization, generating segregant populations with the advancement of generations segregating it is possible to select the best lines of pepper plants with desirable characteristics for ornamental. The objective of this study was to evaluate the genetic diversity among and within the F4 populations of pepper plants, selecting families and promising genotypes for ornamental peppers. The experiment was carried out in a greenhouse at the Laboratory of Plant Biotechnology at the Center of Agricultural Sciences at the Federal University of Paraíba (CCA-UFPB). Were used ten families and four attestant additional of peppers for characterization morphoagronomic based on qualitative and quantitative descriptors. The experimental design was entirely randomized. The experimental unit consisted of one plant per pot. In the first chapter we used 16 quantitative descriptors of plant and fruit, the data were submitted to analysis of multivariate variance, the relative importance was determined by the Singh method, analysis of canonical variables and the Scott-Knot test. In the second chapter qualitative and quantitative and mixed descriptors were used. To quantify the relative contribution of traits to genetic divergence, the Singh criterion was used. Then, the Tocher grouping method was used based on the generalized Mahalanobis distance in the quantitative variables. In the qualitative variables, the Gower distance was used and later a mixed analysis was performed with the qualitative and quantitative data. In addition, non-metric multidimensional scaling was applied. All analyzes were performed with R version 3.0.3 software. In the first chapter by the Singh method it was determined that seven of the sixteen characteristics contributed with 62.70% of the genetic divergence. In the analysis of canonical variables, the first two canonical variables explained 68.05% of the families' discrimination and through the Scott-Knott test the families were grouped into 8 groups. The families that presented the desirable characteristics for ornamental pots were 17.18, 30.16, 30.22, 17.15 and 55.45. In the second chapter the genotypes were evaluated within each family and found that there is genetic diversity within the families analyzed, being possible to practice selection. The family 47.26 was the only one that did not present genotypes with ornamental size to be cultivated in smaller pots, since their plants presented high size.